2017
DOI: 10.1159/000454889
|View full text |Cite
|
Sign up to set email alerts
|

Primary Retinal Detachment Surgery: Changes in Treatment and Outcome in an Austrian Tertiary Eye Center

Abstract: Purpose: The surgery of choice for primary retinal detachment (RD) has shifted towards primary vitrectomy (PPV) in recent years. In this study, 2 cohorts of consecutive patients, treated by 8 retinal surgeons within a 7-year time span were compared. Methods: Baseline demographic data, surgical procedure, and outcome of patients with primary RD surgery between January 2007 and December 2008 (group 1, G1) and January 2012 and December 2013 (group 2, G2) were compared. Statistical analysis included univariate com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The recurrence rates associated with PPV and scleral buckle were 29% and 25.6%, respectively, the difference not being statistically significant. These results highlight the recent changes in trends in RD surgery, favouring with a growing tendency to PPV over scleral buckle as the preferred surgical technique [ 15 ]. In a Cochrane library systematic review comparing PPV and scleral buckle for repairing simple rhegmatogenous detachment, the authors found a rate of redetachment after PPV of 21%, lower than our results [ 2 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The recurrence rates associated with PPV and scleral buckle were 29% and 25.6%, respectively, the difference not being statistically significant. These results highlight the recent changes in trends in RD surgery, favouring with a growing tendency to PPV over scleral buckle as the preferred surgical technique [ 15 ]. In a Cochrane library systematic review comparing PPV and scleral buckle for repairing simple rhegmatogenous detachment, the authors found a rate of redetachment after PPV of 21%, lower than our results [ 2 ].…”
Section: Discussionmentioning
confidence: 68%
“…This is a strikingly high result in comparison with the rest of the medical literature. In most cases, our patients underwent PPV, with a smaller percentage being treated with scleral buckling than in other series [ 15 , 26 ]. Some studies have suggested that scleral buckle surgery has some advantages in inferior RD [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 82%
“…The safety of vitreous surgery has improved in recent years with the introduction of the high-speed vitreous cutter and micro incision vitreous surgery [ 9 ]. Furthermore, the use of wide-angle observation systems during vitrectomy has reduced the invasiveness of macular surgery [ 10 12 ]. It is possible to spontaneously close the scleral wound without suturing by deliberately leaving the vitreous at the periphery to reduce retinal contact during the procedure [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the anatomical success rate of the vitreoretinal surgeries, especially pars plana vitrectomy (PPV), has improved over the past years, the rhegmatogenous retinal detachment (RRD) surgery of high-myopic eyes is still challenging for the vitreoretinal surgeons. Shifting of the primary surgical approach for RD towards PPV has been also observed [5]. The surgery of high-myopic eyes differs from nonhigh-myopic eyes due to the following facts: the very long axial length, the fragile and thin sclera, the choroidal hemodynamic changes with an increased risk of the subretinal and choroid haemorrhage, the choroidal detachment, the anomalous posterior vitreous detachment with the high prevalence of vitreoschisis, the pathologic vitreoretinal attachments with higher retinal break occurrence, as well as the irregularity of the posterior border of the vitreous base.…”
Section: Introductionmentioning
confidence: 92%